2018
DOI: 10.1007/s10029-018-1800-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical technique and outcomes of transabdominal preperitoneal inguinal hernia repair after radical prostatectomy: dissection between the transversalis fascia and superficial layers of preperitoneal fascia

Abstract: In TAPP for patients following prostatectomy, surgery can be performed safely and reliably without prolonging the operative duration by selecting a skilled practitioner and standardizing the technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…This is because the wide preperitoneal dissection took a substantial amount of time. Even compared with other studies, 20 , 21 the operative time of TAPPH + IPTR in our study was very short. TAPPH + IPTR is fast and results in few recurrences and complications.…”
Section: Discussioncontrasting
confidence: 75%
“…This is because the wide preperitoneal dissection took a substantial amount of time. Even compared with other studies, 20 , 21 the operative time of TAPPH + IPTR in our study was very short. TAPPH + IPTR is fast and results in few recurrences and complications.…”
Section: Discussioncontrasting
confidence: 75%
“…The Retzius space is a potential retropubic space situated between the bladder and the pubic bone. Its boundaries include the transversalis fascia anteriorly, the preperitoneal fascia (or super cial umbilical bladder fascia) posteriorly [4,6,14,15], and the inferior epigastric vessels laterally. The identi cation of the second plane is based on the presence of avascular connective tissue that resembles a white spider web, which is considered signi cant and often referred to as the "holy planes" [5].…”
Section: Discussionmentioning
confidence: 99%
“…Proper positioning of the mesh within the preperitoneal space is crucial for effective inguinal hernia repair. The mesh should be placed with half in the Retzius space, between the super cial preperitoneal fascia and the retropubic transversalis fascia, and half in the Bogros space, between the deep preperitoneal fascia and the peritoneum [15]. This placement ensures complete coverage of the hernia defect and minimizes the risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…However, radical prostatectomy (RP) can result in the development of postprostatectomy inguinal hernias (PIH), the estimated incidence rates of which were reported as 4.2%-15.9% following surgery [7,8]. A recent report showed that TAPP for PIH is potentially reliable without prolonging the duration of operation [9]. However, the appropriate approach and repair method of the surgical procedure for PIH remains controversial because of surgical di culty arising from preperitoneal adhesion.…”
Section: Introductionmentioning
confidence: 99%